(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The last few months have been totally disruptive for teaching in Panama - and around the world. The response of the Panamanian public system - and of the states - has been dysfunctional and surprising at first and calmer as the months have passed, but this has led to learning what teachers should be like in the future for the new educational system that is coming, according to understanding of the lessons learned this will be the State’s response , so ’before we give a definite opinion about education that we think is preferable, we should have some idea of the kind of person we want to produce’. In essence we ask ourselves whether teachers should continue to promote dual intellectual and character education in our students and use new technologies as one more tool, that is, a very useful tool (virtual platforms, videoconferencing programs, etc.) or on the contrary new technologies are already an essential part of teaching and are not a more useful tool, so all our students and all our teachers must be technological.